Etnomatematika Permainan Tradisional Provinsi Bengkulu “Bubu Gilo” dalam Konsep Kesejajaran - Jannah, Fitri Zahrotul; Risnanosanti, Risnanosanti; Riwayati, Selvi (Jurnal Pendidikan Matematika : Judika Education, 2024)
This research aims to identify mathematical concept in the traditional game called “Bubu Gilo” in Bengkulu with focus on discussing the concept of parallelism. This research uses descriptive qualitative research methods and an etnhographic approach method using project selection, asking questions, collecting data, analyzing data, and writing. This research was carried out at the place where Bubu are made and in communities that still preserve the traditional game of Bubu Gilo. The research results show that the structure of Bubu Gilo has properties and characteristics that fulfill the concept of parallelism. So it can be used as an example to understand the concept of parallelism. By analyzing the structure and rules of Bubu Gilo, the researcher highlights the involvement of mathematics in the game as an effective informal education tool. Keywords: Bubu Gilo; Ethnomathematics; Parallelism.